Partially Observed Discrete-valued Time Series - Lakhdar Aggoun; Lakdere Benkherouf; Ali Benmerzouga (Электронное моделирование, 2007)
The analysis of time series of counts is a rapidly developing area. It has very broad application in view of the host of integer-valued time series which cannot be satisfactorily handled within the classical framework of Gaussian- like series. In this paper we derive recursive filters for partially observed discrete-valued time series. These processes are regulated by thinning binomial and multinomial operators (to be defined below).